Variability of Morphological Traits of European Beech (Fagus sylvatica L.) Seedlings in Serbia - Popović, Vladan (Array, 2021)
The results of interpopulation variability of morphometric parameters of European beech (Fagus sylvatica L.) seedlings originating from eight populations from the part of natural distribution area in Serbia are presented in this paper. The studied populations of Dubašnica, Jastrebac, Boranja, Fruška Gora, Mali Pek, Goč, Beljanica, and Javor have various ecological and vegetational characteristics. The results of this paper refer to root collar diameter and height of seedlings at the age of 1+0 and 2+0. Analysis of variance showed a statistically significant difference between the populations in terms of the studied morphological traits of seedlings (p